2019
DOI: 10.1007/s13139-019-00608-8
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Radioiodine Treatment within 9 Months from Diagnosis Significantly Reduces the Risk of Relapse in Low-Risk Differentiated Thyroid Carcinoma

Abstract: PurposeAlthough postoperative radioiodine (RAI) therapy has been used in patients with differentiated thyroid carcinoma (DTC) for many years, there is still lack of data defining the timing of RAI administration. A retrospective analysis was carried out to answer the question whether the time of postoperative RAI treatment demonstrated any impact on long-term outcomes, particularly in low-risk DTC.MaterialThe analyzed group involved 701 DTC patients staged pT1b-T4N0-N1M0, who underwent total thyroidectomy and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…In routine practice, the time for patients from finishing enhanced CT examination to starting RAI therapy is far more than 43 days. Moreover, the majority of studies showed that the timing of post-thyroidectomy initial RAI therapy did not affect the overall survival or long-term outcomes (33)(34)(35)(36)(37)(38). Therefore, RAI administration may be safely planned according to the logistics of the local health and the patient itself.…”
Section: Discussionmentioning
confidence: 99%
“…In routine practice, the time for patients from finishing enhanced CT examination to starting RAI therapy is far more than 43 days. Moreover, the majority of studies showed that the timing of post-thyroidectomy initial RAI therapy did not affect the overall survival or long-term outcomes (33)(34)(35)(36)(37)(38). Therefore, RAI administration may be safely planned according to the logistics of the local health and the patient itself.…”
Section: Discussionmentioning
confidence: 99%
“…14 Several studies have shown no difference in short clinical responses or overall survival (OS) between early and delayed RAI. [15][16][17][18] While other studies advocated that a delayed RAI may cause poor OS for DTC patients after 5 or 10 years follow-up compared with early RAI therapy, 9,21 or claimed that applying RAI therapy within 3 months could decrease ablation success. 9 Based on the above contradictory and one-sided reports, we therefore conducted a cohort study to illustrate whether early or delayed treatment of RAI affects the prognosis of DTC patients, and incorporate these results into the current body of evidence by performing a meta-analysis.…”
Section: Introductionmentioning
confidence: 99%
“… 14 Several studies have shown no difference in short clinical responses or overall survival (OS) between early and delayed RAI. 15 , 16 , 17 , 18 While other studies advocated that a delayed RAI may cause poor OS for DTC patients after 5 or 10 years follow‐up compared with early RAI therapy, 9 , 21 or claimed that applying RAI therapy within 3 months could decrease ablation success. 9 …”
Section: Introductionmentioning
confidence: 99%
“…In patients with differentiated thyroid cancer (DTC), stimulated serum thyroglobulin (Tg) concentration measured around the time of radioiodine (RAI) treatment is a valuable prognostic factor for persistent/recurrent disease [1][2][3][4][5]. Given the analyte's approximately 65-h half-life, serum Tg levels should in theory drop to undetectable approximately 1 month after total thyroidectomy.…”
Section: Introductionmentioning
confidence: 99%